RETRACTED : The Influence of Tax Knowledge, Tax Obligation Rights, and Tax Sanctions on Fulfilling Tax Obligations of Umkm in Baktijaya District, Depok City - Nabila Aura Hany; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
This study aims to determine the influence of Tax Knowledge, Tax Obligation Rights, and Tax Sanctions on the Fulfillment of UMKM Tax Obligations in Baktijaya Village, Depok City. This research data uses primary data in the form of questionnaires to 130 MSME respondents. Data analysis techniques use inferential analysis with multiple linear regression and use the Statistical Product and Service Solution (SPSS) program version 26.0. The results of multiple linear regression analysis show that the variables of Tax Knowledge (X1), Tax Obligation Rights (X2), and Tax Sanctions (X3) have a positive and significant effect on the Fulfillment of UMKM Tax Obligations (Y). The results of this study hope that MSMEs can find out Tax Knowledge, Tax Obligation Rights, and Tax Sanctions that can support taxation.